PENGEMBANGAN SISTEM INFORMASI AKADEMIK TERPADU (SIKADU) BERBASIS PERILAKU PENGGUNA DOSEN UNTUK MENINGKATKAN KINERJA AKADEMIK UNNES - Asrori, Asrori (Dinamika Pendidikan, 2010)
The objective of this study is to analyze the development of Integrated Academic Information System (Sistem Informasi Akademik Terpadu/SIKADU) at Semarang State University (UNNES) especially on lecturers as the user. Then, the research problem is there any influence of SIKADU as task-technology fit and utilization toward the lecturersâ performance in doing academic tasks? Thus; the aim of the study is to explain the influences of SIKADU for task-technology fit and utilization by using Technology-to-Performance Chain (TPC) model. The sample of this study was 90 UNNES lecturers as the SIKADU user selected by sample random sampling (SRS). The data was collected by questionnaire method, and then analyzed by multiple linier regressions. The result of the research showed that the task-technology fit and utilization of SIKADU was positively significant influencing the performance of UNNES lecturers to perform their academic tasks. Therefore; based on task-technology fit and utilization theory, the result of the research empirically supported the development of SIKADU at UNNES especially on lecturers as the users.Â Â